The Importance of Olive in Athletes - Taştan, Pelin (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2021)
Olive has many important pharmacological activities such as anticancer, hypoglycemic, hypocholesterolemic, anti-inflammatory and anticancer because of its phenolic compound content. Due to its importance, it is grown in many regions, especially in the Mediterranean region, and studies on it are continued. In addition, olives are important components in the daily diet of a large part of the world's population. Nutrition is an important part of the preparation of active people and athletes for exercise. Athlete nutrition, on the other hand, is a special nutrition program prepared for the development of both the training of the athletes and their athletic performance during the competition, according to the sports branch they are doing. It is very important to include foods with important pharmacological activities that will also benefit the athlete's activities in this nutrition program. In this study, antioxidant activity studies were carried out on olive leaves, which were collected from Ödemiş, İzmir and dried under suitable conditions. Accordingly, DPPH and ABTS capacities and total phenolic content that supports these activities were determined. As a result of the experiments, the EC50 value for the DPPH capacity of the olive leaf extract used in the study was determined as 16,774 ± 0.25 µg/mL, the ABTS capacity was determined as 73.625 ± 0.49 µmol/g and the total phenolic content was determined as 39.26 ± 1.12 mg gallic acid equivalent / g. With this study, which will also contribute to the literature studies, the importance of olive in the sports nutrition program has been emphasized.